Assessing Natural Substrates for Restricting Movement of California Sea Cucumbers Parastichopus californicus. (25th July 2018) - Haddad, Colleen A.; Cross, Stephen F.; Davies, Hailey L.; Duff, Stefanie D.; Fortune, Angela C.; Pearce, Christopher M.
Abstract: California sea cucumbers Parastichopus californicus are reported to prefer hard over soft substrates and can be found associated with shell hash at bivalve farms. We predicted that soft substrates and oyster shells might restrict the movement of sea cucumbers and tested this hypothesis in a laboratory experiment. Small (contracted length, ~4.5 cm) and large (~10 cm) sea cucumbers were placed in the middle of tanks on a uniform, hard substrate (30 × 30‐cm PVC sheet) surrounded by various substrates: no substrate (control); silt, fine sand, and very coarse sand (grain sizes: 2–50 μm, 100–250 μm, and 1–2 mm, respectively); and Pacific oyster Crassostrea gigas shells (~10‐cm border around the PVC sheet) with or without silt surrounding the shells. Movement of individuals was monitored over 24 h in six replicate trials. The mean percent (±SE) of sea cucumbers remaining on the PVC sheet was not significantly different among the control (22 ± 7%), silt (28 ± 8%), fine sand (37 ± 8%), and very coarse sand (20 ± 7%) treatments. Low percentages (<40%) indicated that the animals were not averse to emigrating to the soft substrates. However, significantly more sea cucumbers remained on the hard substrates (PVC and oyster shells) in the treatments comprised of oyster shell (83 ± 7%) and silt with oyster shell (82 ± 8%) than on the PVC sheet in the soft substrate treatments, indicating an affinity of the sea cucumbers for the oyster shells. Significantly more small individuals (95 ± 5%) than large ones (69 ± 9%) remained on the hard substrates. This study demonstrates that soft substrates do not prevent the movement of sea cucumbers under laboratory conditions, while oyster shells may cause a decrease in movement, which has implications for benthic ranching of commercially‐farmed sea cucumbers.